Optimum selection of phase change material for solar box cooker integrated with thermal energy storage unit using multi-criteria decision-making technique. (August 2021) - Anilkumar, B.C.; Maniyeri, Ranjith; Anish, S.
Highlights: Selected the optimum phase change material (PCM) for thermal energy storage (TES) integrated with solar box cooker (SBC) using various multi-criteria decision making (MCDM) methods. Optimum mass of PCM and dimensions of the TES unit required for the SBC to operate for some specific duration is calculated by using a simple iterative procedure developed with MATLAB. Both analysis recommend erythritol as the best PCM for the SBC incorporated with TES unit. Abstract: Various thermal energy storage (TES) materials are used to increase the efficacy of solar cooker in off-sun hours. For the past few decades, phase change materials (PCMs) used as heat storage medium have become research interest. Selection of optimum PCM is important for the effective and efficient heat storage. Therefore, the main objective of the current study is to select the optimum PCM among the alternatives to be used for TES unit incorporated in solar box cooker (SBC). The PCMs are pre-screened among the alternatives used in earlier works based on the melting temperature. The optimum PCM is then selected with the aid of different multi-criteria decision -making (MCDM) techniques like TOPSIS, EDAS and MOORA. The criteria weights required for the optimization algorithm is found by using AHP, ENTROPY and CRITIC methods. Also, compromised values between the weights obtained through these methods are computed. The optimization algorithms are solved using MATLAB. The results of all MCDM techniques show that erythritol is the best alternative for the TES medium incorporated in the SBC. Further, the optimum mass of PCM and dimensions of the TES unit required for the SBC to operate during sun down hours for some specific duration is calculated by using a simple iterative solver developed with MATLAB. There is good agreement between the computational procedure and experimental study using paraffin wax as the TES medium. The iterative solution procedure also selects erythritol to be the best alternative as it required lesser quantity compared with other PCMs. Therefore, we recommend erythritol as the best PCM for the SBC incorporated with TES unit.